Effects of Esketamine on Acute and Chronic Pain After Thoracoscopy Pulmonary Surgery Under General Anesthesia: A Multicenter-Prospective, Randomized, Double-Blind, and Controlled Trial - Lei, Yishan; Liu, Huayue; Xia, Fan; Gan, Shulin; Wang, Yulan; Huo, Wenwen; Wang, Qinyun; Ji, Fuhai (Frontiers in Medicine, 2021)
Background: Postoperative pain management for patients undergoing thoracoscopy surgery is challenging for clinicians which increase both health and economic burden. The non-selective NMDA receptor antagonist esketamine possesses an analgesic effect twice that of ketamine. The application of esketamine might be beneficial in alleviating acute and chronic pain after thoracic surgery. The current study describes the protocol aiming to evaluate the analgesic effect of esketamine after pulmonary surgery via visual analog scale (VAS) score for acute and chronic pain. Methods: A multi-center, prospective, randomized, controlled, double-blind study is designed to explore the analgesic effect of esketamine in randomized patients undergoing video-assisted thoracoscopic surgery (VATS) with general anesthesia. Patients will be randomly assigned to Esketamine Group (Group K) and Control Group (Group C) in a ratio of 1:1. Group K patients will receive esketamine with a bolus of 0.1mg/kg after anesthesia induction, 0.1mg/kg/h throughout the operation and 0.015mg/kg/h in PCIA after surgery while Group C patients will receive the same volume of normal saline. The primary outcome is to measure the pain intensity through the VAS score at rest and during exercise. The secondary outcome includes complications, ketamine-related neurological side effects, recovery time of bowel function and total amount of supplemental analgesics. Assessing timepoint includes 1, 4, 8, 24, 48hours and on the 7th day, 1 and 3 months after the operation. Discussion: The results of the current study might illustrate the analgesic effect of esketamine for patients undergoing thoracoscopy pulmonary surgery and provide evidence and insight for perioperative pain management. Study Registration: The trial was registered with Chinese Clinical Trial Registry (CHICTR) on Nov 18th, 2020 (ChiCTR2000040012).